Welding complete : techniques, project plans & instructions. - Creative Publishing International (Minneapolis, MN : Creative Pub. International, 2009)
"Explores the practical and decorative aspects of welding, including information on tools, materials, safety and dozens of metalwork projects"--Provided by publisher.
Includes index.
Keywords: Welding; Welding -- Equipment and supplies